Subway tunnel concrete facade defect non-flowing structure repairing adhesive and preparation method thereof
Through reasonable proportioning and mixing technology, a non-flowing structure repair glue for concrete upright defects in subway tunnels was developed, which solved the reduction of thixotropy of existing epoxy resin repair materials under high temperature conditions and repaired vertical wall or top surface defects. The problem of flowing and sagging has achieved efficient and stable repair results.
Patent Information
- Application Number
- CN202411558032.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-02-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing epoxy resin repair materials have reduced thixotropy under high temperature conditions, resulting in reduced construction efficiency. When repairing the defects of concrete tiles in subway tunnels, the repair materials are prone to flow and sag, and cannot effectively repair vertical walls or top surfaces. defect.
A non-flowing structure repair glue for subway tunnel concrete upright defects is used. The repair glue consists of component A and component B. Component A includes pure epoxy resin, modified epoxy resin, reactive diluent, filler, Liquid rheology additives and insulated carbon black, component B includes phenoamine curing agents, polyamide curing agents, fillers, liquid rheology additives, coupling agents and accelerators. Through reasonable proportioning and stirring processes, the thixotropy and mechanical properties of the repair glue are improved, ensuring that it still has a certain thixotropy under high temperature conditions, and does not sag or flow during the construction process.
The stable thixotropy of repair glue under high temperature conditions is achieved, the construction efficiency is ensured, and when repairing the defects of the concrete tilt surface of the subway tunnel, the defects on the vertical wall or top surface can be effectively repaired, avoiding the problems of flow and sagging.
Smart Images

Figure BDA0005117085700000131 
Figure BDA0005117085700000141
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building materials, and relates to a non-flowing structural repair adhesive for a subway tunnel concrete upward face defect, and specifically relates to a non-flowing structural repair adhesive for a subway tunnel concrete upward face defect and a preparation method thereof. Background Art
[0002] With the development of economy and the expansion of traffic scale, subway has become a way to relieve ground traffic congestion. Due to materials, construction, environment and other reasons, subway tunnels or platform concrete walls, top surfaces, pipe segments and other parts may have cracks, holes, falling blocks, honeycomb-like rough surfaces, exposed steel bars, and other defects, causing water seepage on the walls, steel bar corrosion, and accelerated aging of facilities, further endangering the safety and stable operation of the subway. To solve such problems, repair materials are generally applied to the original defects, and the repair materials are mostly epoxy resin materials.
[0003] Epoxy resin is an excellent thermosetting resin. After being mixed and cured with the corresponding curing agent, it has good bonding properties and convenient operation. Its solid body has excellent mechanical properties, electrical insulation properties, acid and alkali resistance, and also has the advantage of low shrinkage. However, due to the high cross-linking density of epoxy resin, it leads to large internal stress, large brittleness of the solid body, and poor impact resistance. These problems can be improved by modifying the epoxy resin and its corresponding curing agent, auxiliary materials, etc.
[0004] In the practice of subway repair, it was found that some epoxy resin repair materials have good fluidity and are easy to flow around, so they can repair defects on the horizontal ground. However, when the defects are on the vertical wall, horizontal top or arch surface, the repair materials that are not fully solidified will flow downward by themselves, thus leaving the area to be repaired, and the defect area cannot be repaired. In order to solve the problem of self-flow and sagging of repair materials and achieve static non-flow, non-sagging and non-collapse of repair materials, thixotropic materials can be used to improve the thixotropy of repair materials.
[0005] Thixotropic materials are fluid when stirred, and are in a gel-like state when stirring stops. They can maintain a certain shape for a long time when static without collapsing, sagging, or flowing, and can regain fluidity after continued stirring. Thixotropic materials can reduce waste and cleanliness problems caused by material dripping and sagging at the construction site. When used in epoxy resin repair materials, on the one hand, they can initially bond with the wall substrate, and on the other hand, they can maintain their shape while spontaneously reacting and curing. After a certain period of time, the epoxy resin repair material is cured and firmly bonded to the wall substrate. At this time, the epoxy resin repair material has a certain degree of hardness and strength. After a period of curing and complete curing, the epoxy resin repair material and the wall substrate are completely bonded together.
[0006] Due to the characteristics of epoxy resin itself, two-component epoxy resin repair materials will begin to self-heat after mixing and stirring, and the more materials are mixed, the greater and faster the heat generated. The epoxy resin repair glue that originally has excellent thixotropy at room temperature will experience a decrease in viscosity at higher temperatures, restore fluidity to a certain extent, and even lose its thixotropy. In order to solve this problem, the curing speed can be appropriately slowed down by adjusting the formula, but this will extend the molding time and maintenance cycle of the epoxy resin repair glue. The heat generation can also be reduced by reducing the amount of repair glue prepared each time, but this will increase the frequency of preparation and reduce the efficiency of on-site construction. Therefore, it is very necessary to develop a repair glue that takes into account the material strength, material high temperature resistance and thixotropy, and construction efficiency requirements.
[0007] The invention patent with publication number CN107879668B discloses an anti-cracking epoxy mortar for rapid repair of expansion joints. The anti-cracking epoxy mortar is mixed with component A, component B and component C. Calculated by weight ratio, component A: component B: component C = 2:1:9-15; calculated by weight ratio, the component A is composed of the following raw materials in parts by weight: 100 parts of bisphenol A epoxy resin; 20-50 parts of AGE epoxy resin active diluent; 50-100 parts of toughening resin; 2-5 parts of silane coupling agent KH560; the component B is an aliphatic modified polyamine curing agent; calculated by weight ratio, the component C is composed of the following raw materials in parts by weight: 100 parts of quartz sand with a particle size of 40 mesh to 160 mesh; 20-40 parts of fly ash with a particle size of 325 mesh. The invention prepares a crack-resistant epoxy mortar by mixing bisphenol A epoxy resin, AGE epoxy resin active diluent, toughening agent acrylic grafted polyurethane resin, aliphatic modified polyamine curing agent and other mortars. It solves the common problem of traditional epoxy mortar being prone to cracking during large-area expansion joint construction, but does not solve the problem of reduced thixotropy of the material under high temperature conditions.
[0008] The invention patent with publication number CN105541180A discloses an epoxy mortar material for bridge expansion joint structure, wherein the epoxy mortar material consists of three parts: liquid A, liquid B and filler, wherein the main components of liquid A are composed of the following mass parts: 90 parts of bisphenol A type E-51 epoxy resin, 10 parts of dodecyl to tetradecyl glycidyl ether, and 10-15 parts of CYH-277; the main components of liquid B are composed of the following mass parts: 25-30 parts of curing agent, 1-3 parts of accelerator, 3-5 parts of coupling agent, and 50-70 parts of nonanol; the mass ratio of liquid A, liquid B and filler is 1:1:8; the curing agent is composed of 40 parts of D230 and 60 parts of D2000; the accelerator is one of K54 and DMP-30; the coupling agent is KH-560. The epoxy mortar material of the present invention adopts the combination of a curing agent and a filler such as basalt or slag, taking into account the flexible properties of the curing agent and the hard properties of the filler. After the two are mixed and bonded, they can absorb impact stress and ensure sufficient rigidity. They have stable performance, impact resistance, and durability. They can perform local repairs and overall synthesis, and have good performance. However, they do not solve the problem of reduced thixotropy of the material under high temperature conditions.
[0009] The above technologies do not solve the problem of reduced strength of the repair material and reduced thixotropy under high temperature conditions. In order to solve the above problems, the present invention provides a non-flowing structural repair adhesive for defects on the vertical surface of concrete in subway tunnels. Summary of the invention
[0010] In view of the problems existing in the prior art, the present invention provides a non-flowing structural repair adhesive for defects on the vertical face of concrete in a subway tunnel and a preparation method thereof. The repair adhesive has excellent thixotropy and mechanical properties.
[0011] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0012] In a first aspect, the present invention provides a non-flowing structural repair adhesive for defects on the vertical face of concrete in a subway tunnel, characterized in that it comprises a component A and a component B;
[0013] The component A comprises the following components in parts by weight: 80-120 parts of pure epoxy resin, 10-35 parts of modified epoxy resin, 5-20 parts of active diluent, 2-300 parts of filler I, 0.1-5 parts of liquid rheological additive I, 0.5-5 parts of insulating carbon black and 0.1-5 parts of coupling agent I;
[0014] The component B comprises the following components in parts by weight: 75-100 parts of phenolic amine curing agent, 0-20 parts of polyamide curing agent, 1-150 parts of filler II, 0.1-5 parts of liquid rheological additive II, 0.1-5 parts of insulating carbon black, 0.5-5 parts of coupling agent II and 0-2 parts of accelerator.
[0015] The mass ratio of component A to component B is 1-6:1, preferably 2-5:1.
[0016] The pure epoxy resin in the A component is one or more of bisphenol A epoxy resin, bisphenol F epoxy resin, tetrafunctional epoxy resin and alicyclic epoxy resin. The bisphenol A epoxy resin, bisphenol F epoxy resin, tetrafunctional epoxy resin and alicyclic epoxy resin are all common types on the market and are not limited here. In one embodiment, the bisphenol A epoxy resin can be selected from bisphenol A epoxy resin E51 or bisphenol A epoxy resin E44; the bisphenol F epoxy resin can be selected from bisphenol F epoxy resin 170; the tetrafunctional epoxy resin can be selected from tetrafunctional epoxy resin AG-80; the alicyclic epoxy resin can be selected from alicyclic epoxy resin S-100 or alicyclic epoxy resin S-28. The mass fraction of the pure epoxy resin is preferably 90-100 parts, more preferably 100 parts.
[0017] In the A component, the modified epoxy resin is one or more of nitrile rubber modified epoxy resin, polyurethane modified epoxy resin, and polythiol modified epoxy resin. In one embodiment, the nitrile rubber modified epoxy resin is a liquid carboxyl-terminated nitrile rubber modified epoxy resin, and the epoxy equivalent is 175-390g / eq, selected from one or more of Sanmu SMR-207 and Jiadida 86840, preferably Sanmu SMR-207. In one embodiment, polyurethane modified epoxy resin is one or more of polyurethane modified epoxy resin EPU-302, EPU-303, and EPU-300A with toughening effect. In one embodiment, polythiol modified epoxy resin is a polythiol modified aliphatic epoxy resin, selected from one or more of EPS25 and EPS70, preferably EPS70.
[0018] The active diluent in the A component is one or more of benzyl glycidyl ether, octyl glycidyl ether, C12-14 alkyl glycidyl ether, 1,4-butanediol diglycidyl ether, 1,6-hexanediol diglycidyl ether, ethylene glycol diglycidyl ether, 1,4-cyclohexanedimethanol glycidyl ether, N-(epoxypropyl)-N-phenyl-ethylene oxide methylamine, N,N-diglycidyl-4-glycidyloxyaniline and pentaerythritol glycidyl ether.
[0019] The filler I in the A component is one or more of fumed silica, silica powder, calcium carbonate, calcium sulfate, organic bentonite, hydrogenated castor oil and sulphoaluminate cement. The fumed silica is hydrophobic and has a specific surface area of 150-250 m 2 / g. The fineness of the silicon micropowder is 400 mesh, 600 mesh or 800 mesh, preferably 800 mesh. The calcium carbonate is selected from activated calcium carbonate, heavy calcium carbonate or calcium carbonate whisker; the activated calcium carbonate is hydrophobic calcium carbonate with a fineness of 1250 mesh; the aspect ratio of the calcium carbonate whisker is 20-60. The calcium sulfate can be calcium sulfate whisker, and the aspect ratio of the calcium sulfate whisker is 20-60; the sulphoaluminate cement can be ultrafine sulphoaluminate cement. Preferably, the filler 1 is one or more of fumed silica, silicon micropowder, activated calcium carbonate, calcium carbonate whisker, calcium sulfate whisker and ultrafine sulphoaluminate cement, and further preferably fumed silica, silicon micropowder, activated calcium carbonate and ultrafine sulphoaluminate cement.
[0020] The liquid rheological additive I in the A component is one or more of a polyhydroxycarboxylic acid amide solution, a high molecular weight urea-modified non-polar polyamide solution, and a modified urea solution. The polyhydroxycarboxylic acid amide solution may be RHEOBYK-R 605, the high molecular weight urea-modified non-polar polyamide solution may be RHEOBYK-431, and the modified urea solution may be BYK-410. Preferably, the liquid rheological additive I is RHEOBYK-R 605.
[0021] The insulating carbon black can be a conventional type available on the market, and can be one or more of Orion SPECIAL BLACK 4A, Evonik Degussa NEROX505, Cabot CSX920, Cabot REGAL 250R, Mitsubishi MA7 and Mitsubishi MA-100R. In one embodiment, the insulating carbon black is selected from insulating carbon black Orion SPECIAL BLACK 4A.
[0022] The coupling agent I in the component A is one or both of 3-(2,3-epoxypropoxy)propyltrimethoxysilane and vinyltri(2-methoxyethoxy)silane, preferably 3-(2,3-epoxypropoxy)propyltrimethoxysilane.
[0023] The phenolic amine curing agent in the B component is prepared by a Mannich reaction of a phenolic compound, an aldehyde compound and a basic amine curing agent, wherein the phenolic compound is one or more of phenol, p-tert-butylphenol, phloroglucinol, benzylphenol, dodecylphenol and cardanol, preferably phloroglucinol or cardanol; the aldehyde compound is one or more of formaldehyde, paraformaldehyde, dodecylaldehyde, octadecylaldehyde and benzaldehyde, preferably paraformaldehyde or benzaldehyde; the basic amine curing agent is one or more of hydrogenated meta-phenylenediamine, isophorone diamine, triethylenetetramine, diethylenetriamine, polyetheramine D230, polyetheramine D400 and polyetheramine T-403, preferably isophorone diamine, triethylenetetramine, diethylenetriamine or polyetheramine D230.
[0024] The preparation method of the phenalkamine curing agent is specifically as follows: a phenolic compound and a basic amine curing agent are mixed, stirred for reaction at a temperature of 60-80° C., an aldehyde compound is added, stirred for reflux reaction at 80-90° C. for 2-5 hours, then the temperature is raised to 115-125° C., vacuum distilled for dehydration for 1-2 hours, and the temperature is lowered to 40-60° C. to obtain the phenalkamine curing agent.
[0025] In one embodiment, a phenolic compound and a basic amine curing agent are added to a reactor equipped with an agitator, a reflux condenser, a thermometer, and a dropping funnel, and the temperature is heated to 60-80°C while stirring. The liquid aldehyde compound is slowly added dropwise by opening a liquid separator to avoid excessive reaction and explosion. After the addition is completed, the reaction is stirred and refluxed at 80-90°C for 2-4h. The reactor is then connected to a vacuum distillation device, heated to 115-125°C, and vacuum dehydration is started for 1-2h. The temperature is lowered to 40-60°C to obtain a phenolic amine curing agent.
[0026] In one embodiment, a phenolic compound and a basic amine curing agent are added to a reactor equipped with an agitator, a reflux condenser, and a thermometer, and heated to 60-80° C. while stirring. Solid aldehyde compounds are added in batches, and the reaction is stirred and refluxed at 80-90° C. for 2-4 hours. The reactor is connected to a vacuum distillation device, heated to 115-125° C., and vacuum dehydration is started for 1-2 hours. The temperature is lowered to 40-60° C. to obtain a phenolic amine curing agent.
[0027] The polyamide curing agent in the B component can be a conventional commercially available type, and can be one or more of low molecular weight polyamide 650, polyamide 115, polyamide 6153, preferably low molecular weight, low viscosity polyamide 6153, and the viscosity of the polyamide 6153 in an environment of 25°C is 1300-3500mPa.s.
[0028] The filler II in the B component is one or more of fumed silica, silica powder, calcium carbonate, calcium sulfate, organic bentonite, hydrogenated castor oil and sulphoaluminate cement. The fumed silica is hydrophobic and has a specific surface area of 150-250 m 2 / g. The fineness of the silicon micropowder is 400 mesh, 600 mesh or 800 mesh, preferably 800 mesh. The calcium carbonate is selected from activated calcium carbonate, heavy calcium carbonate or calcium carbonate whisker; the activated calcium carbonate is hydrophobic calcium carbonate with a fineness of 1250 mesh; the aspect ratio of the calcium carbonate whisker is 20-60. The calcium sulfate can be calcium sulfate whisker, and the aspect ratio of the calcium sulfate whisker is 20-60; the sulphoaluminate cement can be ultrafine sulphoaluminate cement. Preferably, the filler II is one or more of fumed silica, silicon micropowder, activated calcium carbonate, calcium carbonate whisker, calcium sulfate whisker and ultrafine sulphoaluminate cement, and further preferably fumed silica, silicon micropowder, activated calcium carbonate and ultrafine sulphoaluminate cement.
[0029] The liquid rheological additive II in the B component is one or more of a polyhydroxycarboxylic acid amide solution, a high molecular weight urea-modified non-polar polyamide solution, and a modified urea solution. The polyhydroxycarboxylic acid amide solution may be RHEOBYK-R605, the high molecular weight urea-modified non-polar polyamide solution may be RHEOBYK-431, and the modified urea solution may be BYK-410. Preferably, the liquid rheological additive II is RHEOBYK-R 605.
[0030] The coupling agent II in the B component is one or more of γ-aminopropyltriethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, and N-(2-aminoethyl)-3-aminopropylmethyldiethoxysilane, preferably γ-aminopropyltriethoxysilane.
[0031] The accelerator in the B component is one or more of 2,4,6-tris(dimethylaminomethyl)phenol, triethanolamine and salicylic acid solution, and the salicylic acid solution is a solution with a mass ratio of benzyl alcohol to salicylic acid of 3:1. In one embodiment, the accelerator is 2,4,6-tris(dimethylaminomethyl)phenol.
[0032] In a second aspect, the present invention further provides a method for preparing the repair glue described in the above technical solution, comprising the following steps:
[0033] 1) preparing component A: pure epoxy resin, modified epoxy resin and reactive diluent are mixed and stirred, coupling agent I and liquid rheological additive I are added and mixed and stirred, filler I is added in batches and mixed and stirred, and finally insulating carbon black is added and mixed and stirred to obtain component A;
[0034] 2) preparing component B: mixing and stirring a phenolic amine curing agent and a polyamide curing agent, sequentially adding a coupling agent II, a liquid rheological additive II, and an accelerator, mixing and stirring, then adding filler II in batches, mixing and stirring, and finally adding insulating carbon black, mixing and stirring, to obtain component B;
[0035] 3) Preparation of repair glue: Mixing component A and component B in a mass ratio of 1-6:1 to obtain the repair glue. Preferably, the mass ratio of component A to component B is 2-5:1.
[0036] The preparation method of component A is as follows: 80-120 parts of pure epoxy resin mixture, 10-35 parts of modified epoxy resin and 5-20 parts of active diluent are mixed by weight, and stirred at 200-400r / m for 10-20 minutes; coupling agent I and liquid rheological additive I are added, and stirring is continued at 300-500r / m for 5-10 minutes. Then 2-300 parts of filler I are added in batches, and the next batch of filler I is added after stirring at 800-1000r / m for 1-2h. Finally, insulating carbon black is added, and stirring is carried out at 800-1000r / m for 20-40 minutes to obtain component A.
[0037] The preparation method of component B is as follows: 75-100 parts of phenolic amine curing agent and 0-20 parts of polyamide curing agent are mixed by weight, and stirred at 200-400r / m for 10-30 minutes; coupling agent II, liquid rheological additive II, and accelerator are added in sequence, and stirred at 300-500r / m for 10-20 minutes; then 2-300 parts of filler II are added, and the next batch of filler II is added after stirring at 800-1000r / m for 1-2h. Finally, insulating carbon black is added, and stirred at 800-1000r / m for 20-40 minutes to obtain component B.
[0038] Compared with the prior art, the present invention has the following beneficial effects:
[0039] First, the repair glue provided by the present invention uses epoxy resin as the basic material for structural repair, and adds modified epoxy resin, carboxyl-terminated nitrile rubber modified epoxy resin, polyurethane modified epoxy resin, and polythiol modified epoxy resin to increase the toughness of the repair glue. Active diluents are used to reduce the viscosity of the system and increase the cross-linking density while reducing the generation of volatiles. Fillers and liquid rheological additives are used to give the repair glue thixotropy. Adding insulating carbon black can improve the thixotropy at high temperatures. At the same time, insulating carbon black also has the function of adjusting the color of epoxy mortar, which is close to the color of the surrounding concrete. Furthermore, a coupling agent is used to make the filler obtain good dispersibility and make the filler and epoxy resin combine well, and a phenolic amine curing agent is used to make the material have excellent bonding properties and mechanical properties.
[0040] Secondly, the repair glue provided by the present invention has excellent thixotropy, excellent bonding ability with concrete and steel bars, small shrinkage of the solid body, excellent mechanical properties, and good toughness; it does not sag or flow when constructed on the upper and lower surfaces; the curing rate at room temperature is fast, but the heat release is slow, and it is not easy to have an implosion phenomenon. It has excellent bonding ability with concrete and steel bars, small shrinkage of the solid body, and excellent mechanical properties. It can also be fully cured when the ambient temperature is low in winter. It still has a certain thixotropy at high temperatures. Even if the repair glue material is accidentally prepared at one time when the ambient temperature is high in summer, the material has a large self-heat so that the temperature rises, and the repair material still does not sag, flow, or collapse, and the construction personnel can operate for a long time. The repair glue provided by the present invention can effectively solve the repair problems of the upper and lower surface block defects of the concrete of subway tunnels, such as concrete block drop, voids, cracks, pockmarks, exposed steel bars, etc. DETAILED DESCRIPTION
[0041] It is worth noting that, unless otherwise specified, the raw materials used in the present invention are all common commercially available products, and their sources are not specifically limited.
[0042] Example 1
[0043] The preparation method of the non-flowing structural repair adhesive for the defective vertical surface of concrete in subway tunnels is as follows:
[0044] (1) Preparation of component A:
[0045] Calculated by weight, a total of 100 parts of bisphenol A epoxy resin E51 were added to the disperser, and then 20 parts of liquid carboxyl-terminated nitrile rubber modified epoxy resin Miki SMR-207, 5 parts of octyl glycidyl ether, and 10 parts of C12-14 alkyl glycidyl ether were added, and stirred at 300r / m for 20 minutes. 2 parts of 3-(2,3-epoxypropoxy)propyltrimethoxysilane and 2 parts of liquid rheological additive RHEOBYK-R 605 were added, and stirring continued at 400r / m for 8 minutes. Then 3 parts of hydrophobic fumed silica were added and stirred at 900r / m for 25 minutes. 150 parts of activated calcium carbonate were prepared, added to the disperser in batches, and stirred at 900r / m for 25 minutes before adding the next batch of activated calcium carbonate, and repeatedly added until all the activated calcium carbonate was completely entered into the epoxy resin. In the same way, add 50 parts of ultrafine sulphoaluminate cement in batches and stir at 900 r / m for 25 minutes. Finally, add 1.5 parts of insulating carbon black SPECIAL BLACK 4A and stir at 900 r / m for 30 minutes to obtain component A.
[0046] (2) Preparation of component B:
[0047] First, prepare the phenalkamine curing agent: Calculate by weight, add 126 parts of phloroglucinol and 103 parts of diethylenetriamine into a reactor equipped with a stirrer, a reflux condenser, and a thermometer, and heat to 70°C while stirring. Prepare 30 parts of paraformaldehyde. To avoid excessive reaction, add the paraformaldehyde to the reaction system in batches, stir and reflux at 85°C for 1.5 hours, then add the next batch of paraformaldehyde, and continue to stir and reflux at 85°C for 1.5 hours. Connect the reactor to a vacuum distillation device, heat to 120°C, and start vacuum dehydration for 2 hours. Cool down to 50°C to obtain the phenalkamine curing agent.
[0048] The preparation method of the B component is as follows: 85 parts of the prepared phenolic amine curing agent and 15 parts of the polyamide curing agent polyamide 6153 are mixed by weight, put into a disperser, and stirred at 300r / m for 20 minutes; 3 parts of γ-aminopropyl triethoxysilane, 0.5 parts of liquid rheological additive RHEOBYK-R 605 and 2 parts of 2,4,6-tris (dimethylaminomethyl) phenol are put into the disperser in sequence, and stirred at 400r / m for 15 minutes; then 3 parts of fumed silica are put in, and stirred at 900r / m for 20 minutes. 40 parts of heavy calcium carbonate are prepared, put into the disperser in 3 batches, stirred at 900r / m for 20 minutes, and then the next batch of heavy calcium carbonate is put in, and the addition is repeated 3 times until all the heavy calcium carbonate is completely entered into the curing agent. According to the same method, 30 parts of ultrafine sulphoaluminate cement were added in batches, and the mixture was stirred at a speed of 900 r / m for 20 minutes before adding the next batch of ultrafine sulphoaluminate cement. Finally, 1 part of insulating carbon black SPECIAL BLACK 4A was added, and the mixture was stirred at a speed of 900 r / m for 30 minutes to obtain component B.
[0049] (3) Preparation of repair glue:
[0050] Mix component A and component B in a mass ratio of 4:1 to obtain a non-flowing structural repair adhesive for defects on the vertical face of concrete in a subway tunnel.
[0051] Example 2
[0052] The preparation method of the non-flowing structural repair adhesive for the defective vertical surface of concrete in subway tunnels is as follows:
[0053] (1) Preparation of component A:
[0054] Calculated by weight, 85 parts of bisphenol F epoxy resin Miki SMF-170 and 15 parts of alicyclic epoxy resin S-28 were added to obtain a total of 100 parts of pure epoxy resin mixture and put into the disperser. Then add 20 parts of polyurethane modified epoxy resin EPU-303, 10 parts of N,N-diglycidyl-4-glycidyloxyaniline, and 10 parts of C12-14 alkyl glycidyl ether, and stir at 300r / m for 20 minutes. Then add 2 parts of 3-(2,3-epoxypropoxy)propyltrimethoxysilane and 2 parts of liquid rheological additive RHEOBYK-R605, and continue to stir at 400r / m for 8 minutes. Add 3 parts of hydrophobic fumed silica and stir at 900r / m for 25 minutes. Prepare 120 parts of activated calcium carbonate, put them into the disperser in batches, stir them at 900r / m for 25 minutes before adding the next batch of activated calcium carbonate, and repeat until all the activated calcium carbonate is completely incorporated into the epoxy resin. Add 40 parts of silicon micropowder in batches in the same way, stir them at 900r / m for 25 minutes. Add 50 parts of ultrafine sulphoaluminate cement in batches in the same way, stir them at 900r / m for 25 minutes. Finally, add 1.5 parts of insulating carbon black Orilon SPECIAL BLACK 4A and stir them at 900r / m for 30 minutes. Component A is obtained.
[0055] (2) Preparation of component B:
[0056] First, prepare the phenalkamine curing agent: Calculate by weight, add 126 parts of phloroglucinol, 83 parts of diethylenetriamine, and 46 parts of polyetheramine D-230 into a reactor equipped with a stirrer, a reflux condenser, and a thermometer, and heat to 70°C while stirring. Prepare 30 parts of paraformaldehyde. To avoid excessive reaction, add the paraformaldehyde to the reaction system in batches, stirring and refluxing at 85°C for 1.5 hours before adding the next batch of paraformaldehyde and continuing to stir and reflux at 85°C for 1.5 hours. Connect the reactor to a vacuum distillation device, heat it to 120°C, and start vacuum dehydration for 2 hours. Finally, cool it to 50°C to obtain the phenalkamine curing agent.
[0057] The preparation method of the B component is as follows: 95 parts of the prepared phenolic amine curing agent and 5 parts of the polyamide curing agent polyamide 6153 are mixed by weight, put into a disperser, and stirred at 300r / m for 20 minutes; 1 part of γ-aminopropyl triethoxysilane, 2 parts of liquid rheological additive RHEOBYK-R 605 and 2 parts of 2,4,6-tris(dimethylaminomethyl)phenol are put in order, and stirred at 400r / m for 15 minutes; then 7 parts of fumed silica are put in, and stirred at 900r / m for 20 minutes. 45 parts of ultrafine sulphoaluminate cement are prepared and put into the disperser in batches, wherein the next batch of ultrafine sulphoaluminate cement is put in after stirring at a speed of 900r / m for 20 minutes, and the addition is repeated 3 times until all the ultrafine sulphoaluminate cement is completely entered into the curing agent. Finally, add 0.3 parts of insulating carbon black ORILON SPECIAL BLACK 4A and stir at a speed of 900 r / m for 30 minutes to obtain component B.
[0058] (3) Preparation of repair glue:
[0059] Mix component A and component B in a mass ratio of 4:1 to obtain a non-flowing structural repair adhesive for defects on the vertical face of concrete in a subway tunnel.
[0060] Example 3
[0061] The preparation method of the non-flowing structural repair adhesive for the defective vertical surface of concrete in subway tunnels is as follows:
[0062] (1) Preparation of component A:
[0063] Calculated by weight, 65 parts of bisphenol A epoxy resin E44, 10 parts of bisphenol F epoxy resin Miki SMF-170, and 25 parts of tetrafunctional epoxy resin AG-80 were added to obtain a total of 100 parts of pure epoxy resin mixture and put into the disperser. Then 20 parts of polyurethane modified epoxy resin EPU-303, 10 parts of N,N-diglycidyl-4-glycidyloxyaniline, and 10 parts of C12-14 alkyl glycidyl ether were added and stirred at 300r / m for 20 minutes. 2 parts of 3-(2,3-epoxypropoxy)propyltrimethoxysilane and 2 parts of liquid rheological additive RHEOBYK-R 605 were added and stirred at 400r / m for 8 minutes. 3 parts of hydrophobic fumed silica were added and stirred at 900r / m for 25 minutes. Prepare 120 parts of activated calcium carbonate, add them into the disperser in batches, stir them at 900r / m for 25 minutes before adding the next batch of activated calcium carbonate, and repeat until all the activated calcium carbonate is completely incorporated into the epoxy resin. Add 50 parts of ultrafine sulphoaluminate cement in batches in the same way, stir them at 900r / m for 25 minutes. Add 1.9 parts of insulating carbon black Orilon SPECIAL BLACK 4A, stir them at 900r / m for 30 minutes, and obtain component A.
[0064] (2) Preparation of component B:
[0065] First, prepare the phenalkamine curing agent: Calculate by weight, add 126 parts of phloroglucinol and 103 parts of diethylenetriamine into a reactor equipped with a stirrer, reflux condenser, thermometer, and dropping funnel, and heat to 70°C while stirring. Then open the liquid separator and slowly add 106 parts of aldehyde compound benzaldehyde to avoid excessive reaction and explosion. After the addition is completed, stir and reflux at 85°C for 3h. Connect the reactor to a vacuum distillation device, heat to 120°C, and start vacuum dehydration for 2h. Cool down to 50°C to obtain the phenalkamine curing agent.
[0066] The preparation method of the B component is as follows: 90 parts of the prepared phenolic amine curing agent and 10 parts of the polyamide curing agent polyamide 6153 are mixed by weight, put into a disperser, and stirred at 300r / m for 20 minutes; 1 part of γ-aminopropyl triethoxysilane, 2 parts of liquid rheological additive RHEOBYK-R 605, and 2 parts of 2,4,6-tris(dimethylaminomethyl)phenol are put in order, and stirred at 400r / m for 15 minutes; 7 parts of fumed silica are put in, and stirred at 900r / m for 20 minutes. A total of 50 parts of ultrafine sulphoaluminate cement are prepared and put into the disperser in batches, wherein the next batch of ultrafine sulphoaluminate cement is put in after stirring at a speed of 900r / m for 20 minutes, and the addition is repeated until all the ultrafine sulphoaluminate cement is completely entered into the curing agent. Finally, add 0.2 parts of insulating carbon black ORILON SPECIAL BLACK 4A and stir at a speed of 900 r / m for 30 minutes to obtain component B.
[0067] (3) Preparation of repair glue:
[0068] Mix component A and component B in a mass ratio of 3:1 to obtain a non-flowing structural repair adhesive for defects on the vertical face of concrete in a subway tunnel.
[0069] Example 4
[0070] The preparation method of the non-flowing structural repair adhesive for the defective vertical surface of concrete in subway tunnels is as follows:
[0071] (1) Preparation of component A:
[0072] Calculated by weight, 10 parts of bisphenol A epoxy resin E44, 5 parts of tetrafunctional epoxy resin AG-807, and 15 parts of alicyclic epoxy resin S-28 were added to obtain a total of 100 parts of pure epoxy resin mixture and put into the disperser. Then 25 parts of liquid carboxyl-terminated nitrile rubber modified epoxy resin Miki SMR-207, 10 parts of 1,4-butanediol glycidyl ether, and 10 parts of pentaerythritol glycidyl ether were added, and stirred at 300r / m for 20 minutes. 2 parts of 3-(2,3-epoxypropoxy)propyltrimethoxysilane and 3 parts of liquid rheological additive RHEOBYK-R 605 were added, and stirring continued at 400r / m for 8 minutes. 2 parts of hydrophobic fumed silica were added and stirred at 900r / m for 25 minutes. Prepare 120 parts of activated calcium carbonate in batches and put them into the disperser in batches. Stir at 900r / m for 25 minutes before adding the next batch of activated calcium carbonate. Repeat this process several times until all the activated calcium carbonate is completely incorporated into the epoxy resin. Use the same method to add 40 parts of silica powder in batches, stir at 900r / m for 25 minutes before adding the next batch of silica powder. Use the same method to add 50 parts of ultrafine sulphoaluminate cement in batches, stir at 900r / m for 25 minutes before adding the next batch of ultrafine sulphoaluminate cement. Add 3 parts of insulating carbon black Orilon SPECIAL BLACK 4A and stir at 900r / m for 30 minutes to obtain component A.
[0073] (2) Preparation of component B:
[0074] First, prepare the phenalkamine curing agent: by weight, add 300 parts of cardanol and 146 parts of triethylenetetramine into a reactor equipped with a stirrer, a reflux condenser, and a thermometer, and heat to 70°C while stirring. Prepare 30 parts of paraformaldehyde. To avoid excessive reaction, add the paraformaldehyde to the reaction system in batches, stirring and refluxing at 85°C for 1.5 hours before adding the next batch of paraformaldehyde and stirring and refluxing at 85°C for 1.5 hours. Connect the reactor to a vacuum distillation device, heat it to 120°C, and start vacuum dehydration for 2 hours. Cool down to 50°C to obtain the phenalkamine curing agent.
[0075] The preparation method of the B component is as follows: 85 parts of the prepared phenolic amine curing agent and 15 parts of the polyamide curing agent polyamide 6153 are mixed by weight, put into a disperser, and stirred at 300r / m for 20 minutes; 1 part of γ-aminopropyl triethoxysilane, 2 parts of RHEOBYK-R 605, and 2 parts of 2,4,6-tris(dimethylaminomethyl)phenol are put in order, and stirred at 400r / m for 15 minutes; 7 parts of fumed silica are put in, and stirred at 900r / m for 20 minutes. Then, 50 parts of ultrafine sulfoaluminate cement are prepared and put into the disperser in batches, wherein the next batch of ultrafine sulfoaluminate cement is put in after stirring at a speed of 900r / m for 20 minutes, and the addition is repeated until all the ultrafine sulfoaluminate cement is completely entered into the curing agent. Finally, add 0.2 parts of insulating carbon black ORILON SPECIAL BLACK 4A and stir at a speed of 900 r / m for 30 minutes to obtain component B.
[0076] (3) Preparation of repair glue:
[0077] Mix component A and component B in a mass ratio of 2:1 to obtain a non-flowing structural repair adhesive for defects on the vertical face of concrete in a subway tunnel.
[0078] Example 5
[0079] The difference from Example 1 is that: "85 parts" of phenolic amine curing agent in component B is replaced by "95 parts"; "15 parts" of polyamide 6153 in component B is replaced by "5 parts"; "component A and component B are mixed in a mass ratio of 4:1" is replaced by "component A and component B are mixed in a mass ratio of 4.5:1", and the other steps are the same as in Example 1 to obtain a repair glue.
[0080] Comparative Example 1
[0081] The difference from Example 1 is that hydrophobic fumed silica, activated calcium carbonate and ultrafine sulfoaluminate cement are not used in component A; "component A and component B are mixed in a mass ratio of 4:1" is replaced by "component A and component B are mixed in a mass ratio of 1.5:1", and the other steps are the same as in Example 1 to obtain a repair glue.
[0082] Comparative Example 2
[0083] The difference from Example 1 is that "hydrophobic fumed silica" is not used when preparing component A, and the other steps are the same as those in Example 1 to obtain a repair glue.
[0084] Comparative Example 3
[0085] The difference from Example 1 is that the "liquid rheological additive RHEOBYK-R 605" is not used in the preparation of component A, and the other steps are the same as those in Example 1 to obtain a repair glue.
[0086] Comparative Example 4
[0087] The difference from Example 1 is that "insulating carbon black ORILON SPECIAL BLACK 4A" is not used in preparing component A, and "insulating carbon black ORILON SPECIAL BLACK 4A" is not used in preparing component B. The other steps are the same as in Example 1 to obtain a repair glue.
[0088] Comparative Example 5
[0089] The difference from Example 1 is that "100 parts" of bisphenol A epoxy resin E51 in component A is replaced by "20 parts", 20 parts of liquid carboxyl-terminated nitrile rubber modified epoxy resin Sanmu SMR-207 in the modified epoxy resin is replaced by 100 parts of liquid carboxyl-terminated nitrile rubber modified epoxy resin 86840, and the other steps are the same as in Example 1 to obtain a repair glue.
[0090] Test example
[0091] The sag, operable time, compressive strength, tensile strength, flexural strength, flexural modulus, tensile shear strength, dry concrete bonding strength, and wet concrete bonding strength of the repair glue obtained in Examples 1-5 and Comparative Examples 1-5 were tested respectively.
[0092] The sag (droop) shall be tested in accordance with the provisions of JC / T 482-2003, the operable time shall be tested in accordance with the provisions of GB / T7123.1-2015, the compressive strength, tensile strength, flexural strength and flexural modulus shall be tested in accordance with the provisions of GB / T2567-2008, the tensile shear strength shall be tested in accordance with the provisions of GB / T 7124-2008, and the dry concrete bond strength and wet concrete bond strength shall be tested in accordance with JC / T 1041-2007.
[0093] The test results are shown in Table 1.
[0094] Table 1 Performance of repair adhesives of Examples 1-5 and Comparative Examples 1-5
[0095]
[0096]
[0097] The above test data show that the repair glue of Examples 1-5 has sufficient operating time, excellent compressive strength, tensile strength, flexural strength, flexural modulus and steel-steel tensile shear strength, good bonding strength to both dry and wet concrete, no sagging, low sag, and can well meet the needs of repairing defects on the vertical surface of concrete in subway tunnels.
[0098] Comparing the repair glue of Examples 1-2, both Example 2 and Example 1 have good sag. The epoxy resin in Component A of Example 2 uses low-viscosity bisphenol F epoxy resin Sanmu SMF170 and alicyclic epoxy resin S-28 to replace the bisphenol A epoxy resin E51 in Component A of Example 1, and the amount of silicon powder is increased. Compared with Example 1, polyetheramine D-230 is introduced into the phenolic amine curing agent in Component B of Example 2, and the amount of phenolic amine curing agent in Component B is increased by 10 parts, the reaction speed of the whole system is accelerated, and the operable time is shortened; the amount of polyamide curing agent is reduced by 10 parts, which reduces some toughness, and the compressive strength, tensile strength, and flexural strength are increased. The bonding performance of polyurethane modified epoxy resin is better than that of carboxyl-terminated nitrile rubber modified epoxy resin and bisphenol A epoxy resin E51 (Example 1), and the dry and wet concrete bonding strength and tensile shear strength of Example 2 are increased.
[0099] Comparing the repair glue of Example 1 and Example 3, Example 3 still has good sag. In the component A of Example 3, the epoxy resin is mixed with 65 parts of bisphenol A epoxy resin E44, 10 parts of low-viscosity bisphenol F epoxy resin, and 25 parts of high-hardness and high-strength tetrafunctional epoxy resin AG-80, replacing 100 parts of bisphenol A epoxy resin in Example 1. In Example 3, N, N-diglycidyl-4-glycidyloxyaniline is a trifunctional active diluent, and the overall crosslinking density in the system is increased. Compared with Example 1, the amount of phenolic amine curing agent in component B of Example 3 is increased by 5 parts, and polyamide 6153 is reduced by 5 parts, resulting in a decrease in overall toughness. Compared with Example 1, the compressive strength of Example 3 increases, and the tensile strength and flexural strength increase. In Example 3, the polyurethane-modified epoxy resin better wets the substrate, and the dry, wet concrete and tensile shear strength increase.
[0100] Comparing the repair glue of Example 1 and Example 4, Example 4 still has good sag. In the A component of Example 4, 10 parts of bisphenol A epoxy resin E44, 75 parts of tetrafunctional epoxy resin AG-80, and 15 parts of low-viscosity alicyclic epoxy resin S-28 are used to replace 100 parts of bisphenol A epoxy resin E51 in Example 1, and tetrafunctional active diluent pentaerythritol glycidyl ether is added, which greatly increases the crosslinking density, compressive strength, tensile strength, and flexural strength. The amount of liquid carboxyl-terminated nitrile rubber modified epoxy resin Miki SMR-207 in Example 4 is increased by 5 parts, and the tensile strength, flexural strength, etc. are reduced to a certain extent. Example 4 reduces the amount of fumed silica by 1 part, increases the liquid rheological additive RHEOBYK-R 6051 parts, adds 40 parts of silicon micropowder, and reduces 30 parts of active calcium carbonate, which has no effect on the overall thixotropy.
[0101] Comparing the repair glue of Example 1 and Example 5, Example 5 still has good sag. In the component B of Example 5, there are 95 parts of phenolic amine curing agent and 5 parts of polyamide 6153. As the amount of phenolic amine curing agent increases, the content of polyamide curing agent decreases, the cross-linking density increases, the compressive strength, tensile strength, and flexural strength increase, the thixotropy does not change, the curing speed becomes faster, and the operable time becomes shorter. The content of polyamide curing agent decreases, resulting in a decrease in toughness, which has a reduced effect on the bonding strength.
[0102] Compared with Example 1, in Comparative Example 1, no filler was used in component A, and the thixotropic property was severely reduced, and the sag flow was greatly increased.
[0103] Compared with Example 1, in Comparative Example 2, hydrophobic fumed silica is not used in component A, the thixotropic property is reduced, and the sag degree is increased.
[0104] Compared with Example 1, in Comparative Example 3, liquid rheological agent RHEOBYK-R 605 is not used in component A, so the thixotropic property is reduced and the sag is increased.
[0105] Comparative Example 4 Compared with Example 1, neither component A nor component B uses insulating carbon black Orion SPECIAL BLACK 4A. The thixotropic property decreases, and the sag increases.
[0106] Comparative Example 5 Compared with Example 1, the bisphenol A epoxy resin E51 in component A is reduced from 100 parts to 20 parts, and 20 parts of the liquid carboxyl-terminated nitrile rubber modified epoxy resin Sanmu SMR-207 in the modified epoxy resin is replaced with 100 parts of the liquid carboxyl-terminated nitrile rubber modified epoxy resin 86840. The toughness of the system is greatly improved, the cross-linking density is reduced, and the compressive strength, tensile strength, and flexural strength are greatly reduced, which is not suitable for structural repair.
[0107] Finally, it should be noted that the above content is only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Simple modifications or equivalent substitutions of the technical solution of the present invention by ordinary technicians in this field do not deviate from the essence and scope of the technical solution of the present invention.
Claims
1. A non-flowing structural repair adhesive for defects on the vertical surface of concrete in subway tunnels, characterized in that: It includes component A and component B; The component A comprises the following components in parts by weight: 80-120 parts of pure epoxy resin, 10-35 parts of modified epoxy resin, 5-20 parts of active diluent, 2-300 parts of filler I, 0.1-5 parts of liquid rheological additive I, 0.5-5 parts of insulating carbon black and 0.1-5 parts of coupling agent I; The B component comprises the following components in parts by weight: 75-100 parts of phenolic amine curing agent, 0-20 parts of polyamide curing agent, 1-150 parts of filler II, 0.1-5 parts of liquid rheological additive II, 0.1-5 parts of insulating carbon black, 0.5-5 parts of coupling agent II and 0-2 parts of accelerator.
2. The repair glue according to claim 1, characterized in that: The pure epoxy resin is one or more of bisphenol A epoxy resin, bisphenol F epoxy resin, tetrafunctional epoxy resin and alicyclic epoxy resin.
3. The repair glue according to claim 1, characterized in that: The modified epoxy resin is one or more of nitrile rubber modified epoxy resin, polyurethane modified epoxy resin and polythiol modified epoxy resin.
4. The repair glue according to claim 1, characterized in that: The active diluent is one or more of benzyl glycidyl ether, octyl glycidyl ether, C12-14 alkyl glycidyl ether, 1,4-butanediol diglycidyl ether, 1,6-hexanediol diglycidyl ether, ethylene glycol diglycidyl ether, 1,4-cyclohexanedimethanol glycidyl ether, N-(epoxypropyl)-N-phenyl-ethylene oxide methylamine, N,N-diglycidyl-4-glycidyloxyaniline and pentaerythritol glycidyl ether.
5. The repair glue according to claim 1, characterized in that: The filler I and filler II are respectively one or more of fumed silica, silica powder, calcium carbonate, calcium sulfate, organic bentonite, hydrogenated castor oil and sulphoaluminate cement; the liquid rheological additives I and liquid rheological additives II are one or more of polyhydroxycarboxylic acid amide solution, high molecular weight urea-modified non-polar polyamide solution and modified urea solution.
6. The repair glue according to claim 1, characterized in that: The coupling agent I is 3-(2,3-epoxypropoxy)propyltrimethoxysilane and / or vinyltri(2-methoxyethoxy)silane.
7. The repair glue according to claim 1, characterized in that: The phenalkamine curing agent is prepared by a Mannich reaction of a phenolic compound, an aldehyde compound and a basic amine curing agent; the phenolic compound is one or more of phenol, p-tert-butylphenol, phloroglucinol, pyrogallol, dodecylphenol and cardanol; the aldehyde compound is one or more of formaldehyde, paraformaldehyde, dodecylaldehyde, octadecylaldehyde and benzaldehyde; the basic amine curing agent is one or more of hydrogenated meta-xylylenediamine, isophoronediamine, triethylenetetramine, diethylenetriamine and polyetheramine.
8. The repair glue according to claim 7, characterized in that: The preparation method of the phenalkamine curing agent is specifically as follows: a phenolic compound and a basic amine curing agent are mixed, stirred for reaction at a temperature of 60-80° C., an aldehyde compound is added, stirred for reflux reaction at 80-90° C. for 2-5 hours, then the temperature is raised to 115-125° C., vacuum distilled for dehydration for 1-2 hours, and the temperature is lowered to 40-60° C. to obtain the phenalkamine curing agent.
9. The repair glue according to claim 1, characterized in that: The coupling agent II is one or more of γ-aminopropyltriethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane and N-(2-aminoethyl)-3-aminopropylmethyldiethoxysilane; the accelerator is one or more of 2,4,6-tris(dimethylaminomethyl)phenol, triethanolamine and salicylic acid solution.
10. The method for preparing the repair adhesive according to any one of claims 1 to 9, characterized in that: The following steps are involved: 1) preparing component A: pure epoxy resin, modified epoxy resin and reactive diluent are mixed and stirred, coupling agent I and liquid rheological additive I are added and mixed and stirred, filler I is added in batches and mixed and stirred, and finally insulating carbon black is added and mixed and stirred to obtain component A; 2) preparing component B: mixing and stirring a phenolic amine curing agent and a polyamide curing agent, sequentially adding a coupling agent II, a liquid rheological additive II, and an accelerator, mixing and stirring, then adding filler II in batches, mixing and stirring, and finally adding insulating carbon black, mixing and stirring, to obtain component B; 3) Preparation of repair glue: Component A and component B are mixed in a mass ratio of 1-6:1 to obtain the repair glue.
Citation Information
Patent Citations
Epoxy mortar for bridge expansion joints and construction method thereof
CN105541180A
A crack-resistant epoxy mortar for rapid repair of expansion joints and its preparation method
CN107879668B
Process for recording discharges in an electrofilter
EP0030320A1
Epoxy structure adhesive for bridge support replacement and preparation method of epoxy structure adhesive
CN111978903A
Cofferdam glue and preparation method thereof
CN115160965A